Isolation and Characterization of Secondary Metabolites in Ethyl Acetate Fraction From Indonesian Eucheuma Spinosum - Inayah, Nurul; Masruri, Masruri (ALCHEMY:Journal of Chemistry, 2023)
AbstractEucheuma spinosum is a type of red algae (Eucheuma) which is used as a food which has a high source of carrageenan. Information on secondary metabolites in E. spinosum is known to have bioactive properties as an antioxidant and antibacterial. The purpose of this study was to isolate and characterize secondary metabolites in E.spinosum. The study was started by isolating secondary metabolites from E.spinosum using Soxhlet extraction followed by solvent partitioning, fractionation and characterization. The rendemen from methanol extract was 6.07% while the highest partition result was in the ethyl acetate fraction, which was 1.25%. Fractionation was carried out by column chromatography resulting in 2 single spots F401 and A402. Pure isolate F401 has an Rf value of 0.71 in the form of a white solid, A401 has an Rf value of 0.67 in the form of a brown gel. The results of characterization of isolates with a UV-Vis spectrophotometer obtained maximum absorption and absorbance values of F401 218.50 nm 4.79 M-1 cm-1, 273 nm 1.06 M-1 cm-1 respectively. Isolate A402 233.50 nm 4.1 M-1 cm-1, 407 nm 1.03 M-1 cm-1. Identification using FT-IR found that both isolates showed the presence of functional groups =C-H, C-C, C=O, C-H. According to the result of the UV and FT-IR spectra, two isolates can be identified as terpenoid compounds. Keywords: E.spinosum, Secondary Metabolites, Ethyl acetate fraction, UV-VIS, FT-IR